1990
DOI: 10.1002/jnr.490270117
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule associated protein (MAP1B) is present in cultured oligodendrocytes and co‐localizes with tubulin

Abstract: Differentiation of oligodendrocytes is accompanied by the extension of processes and the assembly of the myelin membrane. It is likely that the cytoskeleton plays an important role in this process in terms of changes in cell shape, transport of myelin components, and organization of the myelin membrane. Oligodendrocytes contain microtubules (MT) which associate with other components of the cytoskeleton, and microtubule associated proteins (MAPs) may mediate some of these interactions. In this study we have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 59 publications
(101 reference statements)
3
40
0
Order By: Relevance
“…Also, a later decrease in the levels of (phosphorylationindependent) MAP1B has been shown in cultures of hippocampal neurons (Boyne et al, 1995). It is noteworthy that MAP1B is also present in oligodendrocytes (Fischer et al, 1990).…”
Section: Neuronal Cytoskeletal Changes In Pc12 Cellsmentioning
confidence: 88%
“…Also, a later decrease in the levels of (phosphorylationindependent) MAP1B has been shown in cultures of hippocampal neurons (Boyne et al, 1995). It is noteworthy that MAP1B is also present in oligodendrocytes (Fischer et al, 1990).…”
Section: Neuronal Cytoskeletal Changes In Pc12 Cellsmentioning
confidence: 88%
“…First, we compared our database with other studies, primarily the transcriptome database of OLs, neurons, and astrocytes that were isolated from rodent brains (8,(12)(13)(14)(15)(16)(17)(18). Among the 308 proteins, there were at least 111 proteins in our myelin proteome whose mRNA or protein was expressed by OLs (Fig.…”
Section: Protein Identification By Sequential 1-dimensional Page and mentioning
confidence: 99%
“…Many of these transcripts are expressed at higher levels in OL-rich white over gray matter, shown as fold enrichment (i.e., W/G ratio). In addition, to help ascertain the cellular origins of the proteins identified in our proteome, the relative enrichment of their transcripts in purified OLs (red squares in column O), neurons (column N), or astrocytes (column A) was determined through analysis of the transcriptome database of Cahoy et al (8) and other studies (12)(13)(14)(15)(16)(17)(18) of OLs (tan squares in column O). Comparison of the identified proteins in this study with other myelin proteomes (4 -7) has confirmed more than 50% of the identified proteins and revealed the presence of 163 additional proteins in myelin that have not previously been reported in any other proteome (column U).…”
Section: Protein Identification By Sequential 1-dimensional Page and mentioning
confidence: 99%
See 1 more Smart Citation
“…MAP1B expression is markedly upregulated during neurite outgrowth in various types of neurons (Gordon-Weeks and Fischer, 2000), and MAP1B knockout mice exhibit a range of abnormalities in axonal extension and path finding (Meixner et al, 2000;Gonzalez-Billault et al, 2001;Bouquet et al, 2004). More recent studies indicated that MAP1B expression is not restricted in neurons, but also is detected in oligodendrocytes and Schwann cells that produce myelin in the central and peripheral nervous system (CNS and PNS), respectively (Fischer et al, 1990;Ma et al, 1999). In particular, MAP1B expression is elevated in oligodendrocytes that initiate ensheathment of neuronal axons during normal brain development (Wu et al, 2001) as well as in Schwann cells during nerve regeneration (Ma et al, 1999).…”
Section: Introductionmentioning
confidence: 99%